USING INDIRECT CORRECTIVE FEEDBACK TO IMPROVE STUDENTS WRITING ABILITY OF THE FOURTH SEMESTER STUDENTS OF STIK STELLA MARIS MAKASSAR - Syamsir M. (Institut Agama Islam Negeri Palopo, 2016)
This research explored the use of indirect corrective feedback could improve the students writing ability to the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar. The researcher chose two classes of the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar randomly, as the experimental class and the control class. The two classes were given treatment. This paper describes the control class, which was taught with indirect corrective feedback. The data were collected through writing test. The result of the data analysis showed that there was significant difference between the students score who were taught by using indirect feedback and class without indirect corrective feedback. It is proved by the mean score of the experimental class is higher than control class in the posttest. Based on the result, it could be concluded that the use of corrective feedback improved the students writing ability of the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar in academic year 2013/2014.